Fine-grinding Characterisation of PGM Ore Using HIGmill - Mabiza, Audrey (Department of Chemical Engineering, 2023)
Historically, mineral processing industries use conventional tumbling mills to carry out milling operations However, the ore bodies that are currently being explored and mined are low-grade complex ores. These ore bodies often require fine grinding to liberate their valuable fine grained minerals. Conventional mills have proven to be energy inefficient when they are used for fine grinding. Energy efficient technologies, such as stirred mills, are therefore being introduced to the minerals market for use in fine-grinding applications. The HIGmill is an example of a stirred mill that is used for fine grinding mineral ores. This thesis reports the results obtained from the investigating of the influence of operating parameters on the HIGmill product size and specific energy when grinding UG2 platinum ore. The milling experiments were conducted using the HIG 5, which is a laboratory scale HIGmill. The operating variables tested were mill tip speed, solids concentration and grinding media size. Tip speeds tested in this study were between 300 rpm and 1050 rpm. The solids concentration tested was between 40% and 60%. Grinding media sizes used were 2 mm, 3.5 mm and 5 mm. Using these parameters, a three-factorial design was used for the experiments. From the milling results, particle size distributions, stress intensity, specific energy and size specific energy were analysed for each variable tested. Signature plots were also produced for the milling results. Flotation tests were then carried out on the HIG 5 products to assess the downstream response of the HIGmill. The milling results showed that the optimal tip speed was 600 rpm. The optimal solids concentration for the UG2 ore was 60%. For the feed top size of −1000 µm, using 5 mm grinding media was found to be energy intensive and it is recommended that 2 mm and 3.5 mm grinding media are considered when for the grinding the UG2 ore. The flotation results highlighted that grinding finer increases the recovery potential of the ore from 73.2% to an average of 81%. It was also noted that grinding finer increases the chromite recoveries. Flotation kinetic models showed that there is no significant difference in the flotation kinetics of the HIGmill products.